Improved motivation and readiness to quit shortly after lung cancer screening: Evidence for a teachable moment. Issue 10 (10th February 2022) - Williams, Randi M.; Cordon, Marisa; Eyestone, Ellie; Smith, Laney; Luta, George; McKee, Brady J.; Regis, Shawn M.; Abrams, David B.; Niaura, Raymond S.; Stanton, Cassandra A.; Parikh, Vicky; Taylor, Kathryn L.; et al.
Abstract : Background: For patients at high risk for lung cancer, screening using low‐dose computed tomography (lung cancer screening [LCS]) is recommended. The purpose of this study was to examine whether screening may serve as a teachable moment for smoking‐related outcomes. Methods: In a smoking‐cessation trial, participants (N = 843) completed 2 phone interviews before randomization: before LCS (T0) and after LCS (T1). By using logistic and linear regression, the authors examined teachable moment variables (perceived risk, lung cancer worry) and outcomes (readiness, motivation, and cigarettes per day [CPD]). Results: Participants were a mean ± SD age of 63.7 ± 5.9 years, had 47.8 ± 7.1 pack‐years of smoking, 35.2% had a high school diploma or General Educational Development (high school equivalency) degree or less, and 42.3% were undergoing their first scan. Between T0 and T1, 25.7% of participants increased readiness to quit, 9.6% decreased readiness, and 64.7% reported no change ( P < .001). Motivation to quit increased ( P < .05) and CPD decreased between assessments ( P < .001), but only 1.3% self‐reported quitting. Compared with individuals who reported no lung cancer worry/little worry, extreme worry was associated with readiness to quit in the next 30 days (odds ratio, 1.8; 95% CI, 1.1‐3.0) and with higher motivation (b = 0.83; P < .001) at T1. Individuals undergoing a baseline (vs annual) scan were more ready to quit in the next 30 days (odds ratio, 1.8; 95% CI, 1.3‐2.5). Conclusions: During the brief window between registering for LCS and receiving the results, the authors observed that very few participants quit smoking, but a significant proportion improved on readiness and motivation to quit, particularly among individuals who were undergoing their first scan and those who were extremely worried about lung cancer. These results indicate that providing evidence‐based tobacco treatment can build upon this teachable moment. Abstract : During the brief window between registering for lung cancer screening and receiving the results, very few participants quit smoking, but a significant proportion improves on readiness and motivation to quit, particularly among those undergoing their first scan and those extremely worried about lung cancer. These results indicate that providing evidence‐based tobacco treatment can build upon this teachable moment.